Peer assessment approach to promote clinical communication skills in a blended learning course of early clinical exposure - Le, Ho Thi Quynh Anh; Nguyen, Thi Cuc; Nguyen, Thi Thanh Huyen; Ho, Anh Hien; Vo, Duc Toan; Nguyen, Minh Tam; Le, Van Chi (Tạp chí Y Dược Huế, 2022)
Background: Blended learning offers opportunities for the complexity of learning in clinical education. Student peer assessment is widely used as a form of formative assessment in early clinical exposure programs, especially clinical communication skills training. This study aimed to describe clinical communication skills competencies of second-year students and to identify the relationships between peer and faculty assessment of communication skills in a blended learning program format. Methods: A total of 474 second-year general medical students and dental students participated in the study. Peer and lecturer assessment forms with a 5-point Likert scale according to the Calgary-Cambridge guide format were used to evaluate students’ performance of basic communication skills, relationship building, and history taking. Pearson’s correlation coefficients and paired t-test were applied. A p-value < 0.05 was considered statistically significant. Results: Most of students were rated at distinction level (score at 7-8.4) in communication skills. Mean of the overall score by peer and faculty assessment were 7.46 ± 1.03 and 7.17 ± 0.68, respectively. Peers rarely provided negative ratings on subcategories of communication skills. Skills of understanding the patient’s perspectives and gathering information were the most reported skills needed to improve among students. Significant positive correlations were found between peer and faculty evaluations for building relationship, establishing initial rapport, and gathering information domains (p < 0.01). Students tended to grade their colleagues higher for building relationship (3.88 ± 0.62) and establishing initial rapport domains (3.72 ± 0.61) than other domains, meanwhile, teachers tended to grade building relationship (3.80 ± 0.55) and gathering information domains (3.64 ± 0.38) higher than other domains. Conclusion: The findings suggest that student peer evaluation can be valuable for clinical education. As part of a formative assessment, it can be also used for faculty to evaluate students’ clinical communication skills performance in innovative medical education programs.